2012
DOI: 10.1111/j.1526-4610.2012.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Migraine Prevalence, Disability, and Sociodemographic Factors: Results From the American Migraine Prevalence and Prevention Study

Abstract: In the US population, the prevalence of CM was nearly 1%. In adjusted models, CM prevalence was highest among females, in mid-life, and in households with the lowest annual income. Severe headache-related disability was more common among persons with CM and most common among females with CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
396
1
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 444 publications
(432 citation statements)
references
References 25 publications
16
396
1
19
Order By: Relevance
“…Preventive treatment regimens are often critical to ensuring optimal patient outcomes. The goals of migraine preventive therapies include: (1) reduction in attack frequency, severity, and duration; (2) improved responsiveness to acute treatments; (3) decreasing disability and improving overall function; (4) preventing analgesic overuse and “transformation” to chronic daily headache; and (5) reduction of overall cost of treatment 4, 36…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preventive treatment regimens are often critical to ensuring optimal patient outcomes. The goals of migraine preventive therapies include: (1) reduction in attack frequency, severity, and duration; (2) improved responsiveness to acute treatments; (3) decreasing disability and improving overall function; (4) preventing analgesic overuse and “transformation” to chronic daily headache; and (5) reduction of overall cost of treatment 4, 36…”
Section: Discussionmentioning
confidence: 99%
“…The AMPP Study showed that the majority of individuals with CM had not received a correct diagnosis (79.8%) nor specific acute (68.4%) or preventive (60.0%) medications. These data suggest that most patients with CM are not crossing the 3‐step series of barriers and thus are not effectively managed 4, 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent theory, vasoactive neuropeptides released by trigeminal nerve terminals travel to the outer covering of the brain (meninges) causes inflammation and dilation of meningeal blood vessels. Serotonin (5-HT) and magnesium level decreases during migraine which causes vasodilatation and tend to cause migraine attack [12]. According to this concept, calcitonin gene related peptide (CGRP) is a neurotransmitter, which leads to the release of proinflammatory cytokines from the meningeal mast cells cause vasodilatation and leads to migraines headache [1].…”
Section: Pathophysiologymentioning
confidence: 99%
“…4 In Latin America, a multicenter study conducted in Argentina, Brazil, Colombia, Mexico and Venezuela found that 62% of the participants suffered from headaches, and that the prevalence of migraine among women was 6.1% to 17.4%, while that among men was 2.9% to 7.8%. 5 Furthermore, several studies have identified a subgroup of patients who experience chronic migraine, 6,7 in which headache occurs on at least 15 days per month for more than 3 months, 2,8 with features of migraine headache on at least 8 days per month.…”
Section: Introductionmentioning
confidence: 99%